Case Report: Biallelic Loss of Function ATM due to Pathogenic Synonymous and Novel Deep Intronic Variant c.1803-270T > G Identified by Genome Sequencing in a Child With Ataxia–Telangiectasia - Maroilley, Tatiana; Wright, Nicola A. M.; Diao, Catherine; MacLaren, Linda; Pfeffer, Gerald; Sarna, Justyna R.; Billie Au, Ping Yee; Tarailo-Graovac, Maja (Frontiers in Genetics, 2022)
Ataxia-telangiectasia (AT) is a complex neurodegenerative disease with increased risk for bone marrow failure and malignancy. AT is caused by biallelic loss of function variants in ATM, which encodes a phosphatidylinositol 3-kinase that responds to DNA damage. Here, we report a child with progressive ataxia, chorea, and genome instability, highly suggestive of AT. The clinical ataxia gene panel identified a maternal heterozygous synonymous variant (NM_000051.3: c.2250G>A), previously described to result in exon 14 skipping. Subsequently, trio genome sequencing led to identification of a novel deep intronic variant (NG_009830.1(NM_000051.3): c.1803-270T>G) inherited from father. Transcript analyses revealed that c.1803-270T>G results in aberrant inclusion of 56 base-pairs of intron 11. In silico tests predicted a premature stop codon as a consequence, suggesting non-functional ATM; and DNA repair analyses confirmed functional loss of ATM. Our findings highlight the power of genome sequencing and taking into consideration deep intronic variants in undiagnosed rare disease patients.